Sydney Local Health District’s Integrated Response to the COVID-19 Pandemic: A Descriptive Study - Darith Liu; Hueiming Liu; Lou-Anne Blunden; Leena Gupta; Corey Moore; Sven Nilsson; Lisa Parcsi; Miranda Shaw; Teresa Anderson; John Eastwood (International Journal of Integrated Care, 2022)
Introduction: Sydney Local Health District (SLHD) is a local health district in the state of New South Wales in Australia responsible for providing health services to the centre and inner west of the Sydney metropolitan area. SLHD adopted, during the COVID-19 pandemic, an integrated virtual and community care approach to manage quarantine and protect the health and wellbeing of the population. Description: The case study describes the roles of the different agencies and teams in the first six months of the pandemic across four key functions of 1) rapid screening and testing; 2) reaching the community; 3) effective quarantine and ongoing care; and 4) infrastructure, pathology and staff education. Discussion: The “whole of system” approach proved to be an effective method of delivering care that reduced community anxiety, improved and created relationships between existing and new internal and external stakeholders, and changed the community and health sector’s perspective on the importance of virtual care. Conclusion: This case study describes the importance of well-integrated, decentralised and funded public health system in response to the COVID-19 pandemic.